The Functional Copy Number Variation-67048 in WWOX Contributes to Increased Risk of COPD in Southern and Eastern Chinese. (3rd September 2015) - Yang, Lei; Qiu, Fuman; Fang, Wenxiang; Zhang, Lisha; Xie, Chenli; Lu, Xiaoxiao; Huang, Dongsheng; Guo, Yuan; Pan, Mingan; Zhang, Haibo; Zhou, Yifeng; Lu, Jiachun
Abstract: Recent studies have recognized the genetic variants in the WW domain-containing oxidoreductase ( WWOX ) gene as genetic determinants of lung function, reflecting that the WWOX gene may be a susceptible factor of chronic obstructive pulmonary disease (COPD), which characters as poor lung function. We have previously showed that the copy number variation-67048 (CNV-67048) of WWOX was associated with lung cancer risk. Here, we hypothesized that the CNV-67048 affects COPD susceptibility. Based on a two-stage case-control study with a total of 1791 COPD patients and 1940 controls of southern and eastern Chinese, we found that the loss genotypes (0-copy and 1-copy) of CNV-67048 harbored a significantly increased risk of COPD, with an odds ratio (OR) as 1.29 (1.11–1.49) when compared with the common 2-copy genotype. The pre-forced expiratory volume in one second (pre-FEV1 ) to pre-forced vital capacity (pre-FVC) of carriers with loss genotypes (0.729 ± 0.130) was significantly lower than carriers with 2-copy genotype (0.747 ± 0.124; p = 7.93 × 10 −5 ). However, no significant difference was observed on pre-FEV1, pre-FVC and the annual decline of pre-FEV1 between the loss genotypes and 2-copy genotype carriers. Our data suggest that the loss genotypes of CNV-67048 in WWOX predispose their carriers to COPD, which might be a genetic biomarker to predict risk of COPD in Chinese.